PENGARUH PROGRAM RENCANA KONSERVASI TANAH DESA (RKTD) TERHADAP PENGHIDUPAN BERKELANJUTAN PETANI LAHAN KRITIS DI DESA JETIS LOR KECAMATAN NAWANGAN KABUPATEN PACITAN - , Febriana Muryanto ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Jetis Lor village has a total of 215.82 ha of degraded land or 20.4% of the total area of the land. That degraded land affected the sustainable livelihood of the farmers. The sustainable livelihood of the farmers was important to be investigated because 96.50% of Jetis Lor inhabitants depended on the agriculture and silviculture aspects. This research combines between quantitative and qualitative methods. The research sample were 100 respondents of the total number of 925 population who were obtained by using purposive sampling technique based on the certain criteria. The methods of the research were used in the two ways. The method of program implementation conducted by using qualitative descriptive method based on the interview with the informants while the influence between variables conducted by using regression analysis which used the SPSS 17. The results of the research indicated that the implementation of the RKTD program was conducted by using Participatory Action Research, which the subjects and the researcher were the community of Jetis Lor. The implementation of the program began from the socialization and identification of the problems by discussing and establishing the Farmers Conservation Group (KPK). The activities of KPK were studying about the management of the land and breeding, finding a solution, and conservation by using vegetative methods that were crop alley, land cover and planting the crops and trees and by using the mechanical method that were terracing and irrigation canal. Statistical test results revealed that there was an influence between RKTD and the farmersâ livelihood, RKTD variable coefficient was 1.444 means that if the variable of RKTD increased then the farmersâ livelihood variable would increase as 1,444. The R value of 0.781 indicated a strong correlation between the RKTD and the farmersâ livelihood. There was also the influence of RKTD and the sustainable farmersâ livelihood. The coefficient of RKTD variable regression was 0.859 means that if RKTD variable increased, the variable sustainable livelihood would increase as 0.859. The R value of 0.575 indicated that there was the medium correlation between RKTD and a sustainable farmersâ livelihood.